Presynaptic Serotoninergic Regulation of Emotional Processing: A Multimodal Brain Imaging Study. - Selvaraj, S; Mouchlianitis, E; Faulkner, P; Turkheimer, F; Cowen, P; Roiser, J; Howes, O (Elsevier, 2014)
BACKGROUND: The amygdala is a central node in the brain network that processes aversive emotions and is extensively innervated by dorsal raphe nucleus (DRN) serotonin (5-hydroxytryptamine [5-HT]) neurons. Alterations in DRN 5-HT1A receptor availability cause phenotypes characterized by fearful behavior in preclinical models. However, it is unknown whether 5-HT1A receptor availability is linked specifically to the processing of aversive emotions in humans or whether it modulates connectivity in brain networks involved in emotion processing. To answer this question, we investigated the relationship between DRN 5-HT1A receptor availability and amygdala reactivity to aversive emotion and functional connectivity within the amygdala-cortical network. METHODS: We studied 15 healthy human participants who underwent positron emission tomography scanning with [(11)C]CUMI-101, a 5-HT1A partial agonist radioligand, and functional magnetic resonance imaging of brain responses during an incidental emotion processing task including happy, fearful, and neutral faces. Regional estimates of 5-HT1A receptor binding potential (nondisplaceable) were obtained by calculating total volumes of distribution for presynaptic DRN and amygdala. Connectivity between the amygdala and corticolimbic areas was assessed using psychophysiologic interaction analysis with the amygdala as the seed region. RESULTS: Analysis of the fear versus neutral contrast revealed a significant negative correlation between amygdala response and DRN binding potential (nondisplaceable) (r = -.87, p < .001). Availability of DRN 5-HT1A receptors positively correlated with amygdala connectivity with middle frontal gyrus, anterior cingulate cortex, bilateral precuneus, and left supramarginal gyrus for fearful (relative to neutral) faces. CONCLUSIONS: Our data show that DRN 5-HT1A receptor availability is linked specifically to the processing of aversive emotions in the amygdala and the modulation of amygdala-cortical connectivity.